Impact of contrast-induced acute kidney injury on the association between renin-angiotensin system inhibitors and long-term mortality in heart failure patients. (December 2020) - Lei, Li; Huang, Yulu; Guo, Zhaodong; Song, Feier; He, Yibo; Liu, Jin; Sun, Guoli; Liu, Bowen; Chen, Pengyuan; Zhao, Jianbin; Wu, Dengxuan; Xue, Yan; et al.
Introduction: Renin-angiotensin system inhibitors (RASi) reduce mortality among heart failure (HF) patients, but their effect among those complicating contrast-induced acute kidney injury (CI-AKI) remains unexplored. We aimed to investigate whether the relationship between RASi prescription at discharge and mortality differs between HF patients with or without CI-AKI following coronary angiography (CAG). Methods: About 596 HF patients from an observational cohort were divided into a CI-AKI group ( n = 104) and a non-CI-AKI group ( n = 492) based on whether they had CI-AKI following CAG. The endpoint was all-cause mortality. Multivariable Cox regression was performed in each group to explore the associations between RASi at discharge and mortality. Results: During the median follow-up time of 2.26 (1.70; 3.24) years, higher mortality rate was observed in the CI-AKI group compared to the non-CI-AKI group (18.3% vs 8.9%, p = 0.002). Among HF patients with CI-AKI, after adjusting for confounding factors, the association was not significant between RASi prescription at discharge and mortality (HR: 0.39, 95%CI: 0.12–1.31, p = 0.128), while it was among those without CI-AKI (HR: 0.39, 95%CI: 0.18–0.84, p = 0.016). Conclusion: RASi prescription at discharge for HF patients complicating CI-AKI tended to be ineffective, while it benefited those without CI-AKI. Further randomized evidence is needed to confirm this trend.